Jurnal Antika - Kamalia, Antika Zahrotul; Rahendra Herlianto, Hemdani; Rozikin, Zaenur; Andriani (Teknik Informatika, Universitas Pelita Bangsa, 2023)
Education has a crucial role in the development of a nation, and evaluating the quality of education is very important. One of the main indicators in assessing the quality of an educational institution is the school rating. In DKI Jakarta Province, a number of high schools provide a variety of student numbers and quality of education. This research aims to classify the ranking of senior high schools in DKI Jakarta Province based on the number of school students using the Naive Bayes algorithm method. This research method collects data on the number of school students and school ratings from various trusted sources. Then, the data is processed and analyzed using the Naive Bayes algorithm to classify school ratings based on the number of students. The analysis results show that the Naive Bayes algorithm can provide classification school ratings with a satisfactory level of accuracy.